A review of the development and enactment of a radio programme on rainwater harvesting in expanding social learning interactions: a case of the Imvotho Bubomi Learning Network in the Nkonkobe Municipality, Eastern Cape, South Africa - Lupele, Chisala (Rhodes University, Faculty of Education, Department of Education, 2017)
The use of radio and associated information and communications technologies (ICTs) has not been widely explored as a process of environmental education over the years. If environmental education is to involve many people, the use of radio and associated ICTs, particularly in community radio, needs to be researched because radio has multilayered functions. This study examines how practitioners in an agricultural Community of Practice (CoP), namely the Imvotho Bubomi Learning Network in the Nkonkobe Municipality, Eastern Cape, South Africa developed a radio programme on rainwater harvesting for the promotion of food security. The study probes the expansion and social learning of the network and into the public sphere after broadcasts. The study draws on research data generated in the Amanzi for Food project which was funded by the Water Research Commission of South Africa and was led by the Rhodes University Environmental Learning Research Centre. Using interviews, radio programme transcripts and observations, the study found that through using their prior knowledge from a training of trainers' course on rain water harvesting and drawing on everyday experience of rainwater harvesting the CoP members had an expansion in their mutual engagement, joint enterprise, diversity, shared repertoire and identity into a knowledge community. This learning process developed through a successive elaboration of social ecological and social articulations related to the expansive functioning of the CoP; and experience of the benefits of rainwater harvesting as radio programme listeners deliberated how the different practices related to their existing knowledge and experience. The study also found that these expansive processes of social learning occurred across the spectrum of smallholder farmers and homestead food growers in a stimulated radio listening focus group discussion. The study concludes that agriculture practitioners involved in education for sustainable development could expand their knowledge sharing platforms by giving more attention to community radio as a means of both involving participants and engaging learning communities in local environment and sustainability concerns.
Keywords: Imvotho Bubomi Learning Network; Amanzi for Food; Radio in education -- South Africa -- Eastern Cape; Educational broadcasting -- South Africa -- Eastern Cape; Radio stations -- South Africa -- Eastern Cape; Community radio -- South Africa -- Eastern Cape; Environmental education -- South Africa; Water conservation -- Study and teaching -- South Africa; Rhodes University. Environmental Learning Research Centre